Top-down synthesis of luminescent microplastics and nanoplastics by incorporation of upconverting nanoparticles for environmental assessment. Issue 7 (6th June 2022) - Yakovenko, Nadiia; Amouroux, Baptiste; Albignac, Magali; Collin, Fabrice; Roux, Clément; Mingotaud, Anne-Françoise; Roblin, Pierre; Coudret, Christophe; ter Halle, Alexandra
Abstract : Polyethylene model particle is synthesized by a top-down approach with effective incorporation of upconverting nanoparticles. The particles with irregular shapes, similar to those found in the environment, are trackable under 980 nm irradiation. Abstract : The occurrence of micro- and nanoplastics is a major environmental problem. Especially for nanoplastics due to their easy bioavailability and unknown impact on living organisms. The monitoring of these extremely small particles during their ingestion, tissue translocation and transfer through the trophic chain remains very challenging. This study aims to develop an environmentally relevant model of luminescent micro- and nanoplastics. Lanthanide based upconverting nanophosphors able to convert highly penetrating and benign near infrared light into visible one were selected as luminescent tag for the plastic particles. First, lanthanide-based upconverting nanophosphors (20 nm) were incorporated in bulk polyethylene without modification of the polymer structure or morphology. Second, micrometric and nanometric particles were obtained after powdering. Two fractions were obtained with cascade filtration with average sizes of 5 μm and 150 nm and characterized in terms of size distribution, morphology and surface charge. The particles are very polydisperse with an irregular shape and a global negative charge; they exhibit morphological characteristics similar to those formed in the environment. Their luminescent properties upon NIR excitation at 980 nm open the possibility to track them in the tissues of organisms. The powdering method is very simple and compatible with many polymers pure or formulated. As a perspective, the use of weathered materials is possible with the proposed method and will allow the preparation of particles sharing additional properties with environmental micro- and nanoplastics.